(untitled) (Baghdad Science Journal, 2023)
In the current work, aromatic amines and alkyl halides have been converted to the corresponding azides 2a‒d and 4a-d by the reaction with sodium nitrite and sodium azide respectively for amines and sodium azide for halides. Then, dipropargyl ether derivative of D-mannose 8 has been synthesized from diacetone mannose that has been obtained by the treatment of D-mannose (5) with dry acetone in the presence of sulfuric acid. Then, aldol condensation has been used to prepare diol 7 from the mannose diacetonide 6. The reaction of compound 7 with propargyl bromide in alkaline media has been afforded dipropargyl derivative 8. In a parallel step, both dialkyne with aromatic and aliphatic azide have been coupled to produce 1,2,3-triazole derivatives 9a‒d in the presence of Cu(I) salts. All synthesized compounds have been characterized by 1D and 2D NMR spectra alongside with HRMS data. The antibacterial activity against both gram-positive and gram-negative has been tested. Moreover, the anticancer activity has also been evaluated against AMJ13 cell line.